APPLICATION OF TRADITIONALTHEORIES IN THE AGE OF CYBER COMMUNICATION - JIBRIN UMAR OMACHI; COMFORT ENE OBAJE (International Studies Journal)
The advent of cyber communication has raised questions about the applicability of traditional communication theories in the digital age. This position paper critically examines the relevance and adaptability of traditional theories in the context of contemporary digital communication platforms. As communication practices have undergone significant transformations with the proliferation of digital technologies, it becomes crucial to assess the suitability of theories developed in the pre-digital era. Drawing upon influential communication theories such, this paper conducts a comprehensive analysis of their fundamental premises and concepts. It explores the extent to which these theories can effectively explain and analyze communication phenomena within the realm of cyber communication, characterized by social media, online forums, instant messaging, and other digital platforms. Through a synthesis of empirical research and scholarly discourse, this paper highlights the challenges and opportunities associated with the application of traditional theories in the digital age. It argues for the need to adapt and modify these theories to account for the unique characteristics of cyber communication, including networked connectivity, user-generated content, and algorithmic influence. A nuanced understanding of the socio-cultural, technological, and contextual factors shaping digital communication practices is emphasized. It underscores the importance of considering the dynamic interplay between technology, society, and communication processes. By bridging the gap between traditional theories and contemporary digital communication practices, this paper aims to enrich our understanding of the evolving communication landscape.